Cardiac resynchronization therapy improves myocardial conduction. Issue 2 (27th December 2018) - Yang, Mei; Li, Xuping; Yang, Dachun; Li, Yigang; Zhou, Shenghua; Liang, Jinjun; Wu, Gang; Del‐Carpio Munoz, Freddy; Chen, Horng H.; Friedman, Paul A.; Cha, Yong‐Mei
Abstract: Background: Cardiac resynchronization therapy (CRT) reverses left ventricular remodeling and improves left ventricular systolic function. However, little is known about whether CRT improves ventricular conduction. Objective: To determine the relationship between CRT response and QRS narrowing. Methods: The study included consecutive patients who underwent CRT with defibrillator (CRT‐D) implantation between January 2002 and December 2012 and had subsequent generator replacement (GR). At the time of GR, super‐responder was defined as those who had left ventricular ejection fraction (LVEF) of 50% or more; patients who had an LVEF of 36–49% with an increase of more than 5% were considered responders, and the others were nonresponders. All patients were assessed 6 months after CRT‐D implantation and at the time of GR. Results: Of 114 study patients, 58 (50.9%) were nonresponders, 29 (25.4%) responders, and 27 (23.7%) super‐responders. QRS narrowing at 6 months was significant in super‐responders (175.4 ± 21.4 to 159.7 ± 20.7 ms, P  = 0.001) and responders (169.0 ± 21.3 to 157.7 ± 17.6 ms, P  = 0.008). At time of GR, only super‐responders had further QRS narrowing (159.7 ± 20.7 to 146.3 ± 19.2 ms, P  < 0.001). QRS duration change after 6 months was independently associated with super‐response (hazard ratio: 1.20 for every 5 ms QRS duration narrowing; 95% confidence interval, 1.06–1.38; P  = 0.005), and QRS narrowing of 10 ms or more was associated with lower risk of all‐cause mortality after GR. Conclusion: Continuous QRS narrowing after CRT, as an electrical marker, is associated with a super‐response to CRT. Further QRS narrowing 6 months after CRT implantation was associated with lower risk of mortality after GR.